GOP-LeS: Practical Learning Innovation in Managing Office Administration in Groups - Dharma, Buyung Adi; Basuki, Andi; Churiyah, Madziatul; Sakdiyyah, Dewi Ayu (International Education Trend Issues, 2023)
This study aims to produce office simulation media in groups for archives, finance, public relations protocol, and correspondence subjects. The design of this study adopts the Borg and Gall model which consists of 10 stages. This research was conducted in Malang City at the Office Management and Business Service Vocational High School. The trial subjects involved 15 students in the small group trial and 50 students in the large group trial. This research activity also involves expert valiators to determine the feasibility and validity of the products being developed. The results of this research and development are learning media called GOP-LeS that are feasible and valid to be applied in the learning process of managing office administration practices. This is based on the results of small group trials which obtained an average of 86% and large group trials obtained an average of 87%. While the results of the expert validator obtained an average score of 88%. So it can be concluded that the GOP-LeS learning media can be used as an alternative media for the practice of managing office administration in the Department of Office Management and Business Services.